Pemimpin Ideal dalam Cahaya Al Qur’an - Suharnia Wati; Cinta Bayduri Filzah; Taufiq Adek Angga; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Leadership in the Islamic perspective is a sacred trust given by Allah to humans as His vicegerents on earth to prosper the world and safeguard the well-being of the community. Leaders are required to possess key qualities such as honesty, trustworthiness, intelligence, and the ability to convey the truth, as well as being faithful, pious, just, professional, and responsible. The stories of Prophet Adam and Prophet David in the Qur'an illustrate the immense responsibility and the risks of succumbing to desires, which can be overcome through introspection and repentance. An ideal leader should use the Qur'an and hadith as guidance to achieve justice, welfare, and blessings for themselves and their communities, serving as a foundation for happiness in this world and the hereafter.